The Career of Scribes of the Grand Duchy of Lithuania and the Factors That influenced It according to the 1566–1623 Lithuanian Metrics Data - Malašinskienė, Vita (Vilnius University Open Series, 2024)
The article examines what influence the number of signed documents had on the careers of GDL scribes. In order to do this, a statistical method is used in this article. The statistical data (see appendices no. 2 and 3) lead to the conclusion that persons who were active in their daily work were more successful in climbing the career ladder. These are Leonas Sapiega, Gabrielius Vaina, Eustachijus Valavičius (the future bishop of Vilnius) and Aleksandras Gosievskis. These individuals have one thing in common – they all started working in the office at a relatively young age. The conducted research allows to see a connection between a person’s education, his professional activity and a more successful career. However, it is important not to forget the informavo influence as well. For example, M. Vaina was one of the most active scribes of the LDK office, but he did not have an impressive career. The importance and influence of education on the career of a scribe is also illustrated by the case of Valavičius brothers. E. Valavičius surpassed his older brother Jeronimas with having a better education, being more active in the chancellery which allowed him to reach the post of chancellor sooner. This case shows that it didn’t matter how long a person had worked in the office before moving up the career ladder. Consequently, education, activity and the ability to maintain good relations with the social environment were more important for the career of a scribe than the work experience.
Keywords: chancellery; scribe; document; Lithuanian Metrics; Ruthenian; Latin